Audiological manifestations in patients of upper airway allergy - Sekhon, Gurbinder Singh; Verma, Rohit; Munjal, Manish; Chopra, Hemant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The pathophysiology of involvement of inner ear in patients of upper airway allergy is poorly understood. The endolymphatic sac may be the likely seat of involvement in these patients as it can process antigens and produce its own local immune response. The aim of study was to assess the audiological profile of these patients. Methods: 53 patients of upper airway allergy (33 females and 20 males with mean age 25.77 years) and 20 control subjects (9 females and 11 males with mean age of 35.65 years) underwent haematological and audiological assessment. Results: The study group had sensorineural hearing loss at 4000 and 8000 Hz frequencies. Abnormal distortion product otoacoustic emissions (DPOAEs) were noted in the study group as compared with the controls. On auditory brain stem response testing, no statistically significant difference was noted in the absolute latencies of waves I, III and V between study and control groups. Also no statistically significant difference was noted in the wave I-III and wave I-V inter peak latencies between the two groups. Conclusions: We found higher prevalence of high frequency sensorineural hearing loss and abnormalities of DPOAEs in patients having upper airway allergy. The likely seat of damage appears to be the inner ear as evidenced by abnormalities of DPOAEs. However the exact pathophysiology of inner ear damage in patients of upper airway allergy is poorly understood and needs further research.